Kepadatan dan Pola Distribusi Kerang Totok (Geloina erosa) di Perairan Wisata Hutan Payau Cilacap - Amanda Retnaning Diyah; Any Kurniawati; Dewi Kresnasari (Scientific Timeline, 2022)
One of unique biota that lives in Cilacap Mangrove Forest Tourism area is mangrove clam Geloina erosa. Many of these clams are fishing targets by the local community. The clams would be either sold to the market or consumed directly. This study aims to determine the density and distribution pattern of G. erosa in Cilacap Mangrove Forest Tourism area waters, and was conducted in May-June 2021. The research method used was direct observation in the field with purposive sampling technique. There are 3 sampling stations, each of which is observed once every week for 3 weeks. The results shows that the density of G. erosa was 301 ind/m2, 15 ind/m2 and 4 ind/m2 at stations 1, 2, and 3 respectively. The distribution pattern of G. erosa at each observation station was a clustered distribution.